Energy cost of resistance exercises: an update - Reis, V. R.; Junior, R. S.; Zajac, A.; Oliveira, D. R. (Journal of Human Kinetics, 2011)
The use of resistance exercises and of typical strength training methods have been progressively used to control body mass and to promote fat mass loss. The difficulties involved in the energy cost calculation during strength training are associated with the large amount of exercises and their several variations. Mean values between .3 and 30 kcal.min-1 are typically reported but our studies indicate that it may attain values as high as 40 kcal.min-1 in exercises which involve a large body mass. Therefore, in our opinion, the next step in research must be the isolated study of each of the main resistance exercises. Since the literature is scarce and that we do consider that the majority of the studies present severe limitations, the aim of this paper is to present a critical analysis of the energy cost estimation methods and provide some insights that may help to improve knowledge on resistance exercise. It seems necessary to rely on the expired O2 measurements to quantify aerobic energy. However, it is warranted further attention on how this measure is performed during resistance exercises. In example, studies on the O2 on-kinetics at various conditions are warranted (i.e. as a function of intensity, duration and movement speed). As for anaerobic lactic energy, it is our opinion that both the accumulated oxygen deficit and the blood lactate energy equivalent deserve further studies; analyzing variations of each method as an attempt to establish which is more valid for resistance exercise. The quantification of alactic anaerobic energy should be complemented by accurate studies on the muscle mass involved in the different resistance exercises. From the above, it is concluded that knowledge on the energy cost in resistance exercises is in its early days and that much research is warranted before appropriate reference values may be proposed.